Sports Performance and Challenges of Student-Athletes in a Catholic School - Magdato, Erjane P. (Technium Social Sciences Journal, 2021)
This descriptive-correlational study determines the level of sports performance of student-athletes in a Catholic school in Bacolod City during the academic year 2019-2020 in terms of personality traits, sex, types of sport, family monthly income and academic level. It also determines whether a significant relationship exists between the level of sports performance and demographics. Lastly, to identify the multiple challenges face by student-athletes. The results revealed that student-athletes level of sports performance is very satisfactory, which means student-athletes in Catholic school possessed and exceed most of the characteristics of a sport-excellent individual. On the other hand, no significant relationships exist between demographics and level of sports performance. Moreover, all variables do not predict the sports performance of student-athletes. Student-athletes face multiple challenges in the areas of administration, sports, academics, and personal development.